UPAYA PEMERTAHANAN BAHASA AREK SUROBOYO - Fajri, Namira Choirani (Universitas Wijaya Kusuma Surabaya, 2021)
The era of the industrial revolution 4.0 brings convenience to accelerate and expand the distribution of information. For regional languages, this situation can not only be seen as a challenge but also an opportunity. The application of regional languages as a communication tool as well as a marker was captured as an opportunity by one of the regional information accounts, Asli Suroboyo. Among the Instagram accounts based on regional information, AsliSuroboyo is one of the accounts that survives with its trademark, namely using the Javanese dialect of Arek as a medium of communication. The purpose of this study is to describe the efforts to maintain the Javanese dialect of Arek on the AsliSuroboyo Instagram account. The method used is a qualitative descriptive method with primary data sources coming from uploads and captions on Suroboyo's original Instagram account, while secondary data is obtained from a literature study on related topics. The data were analyzed descriptively to examine the relationship between uploads and captions used in the AsliSuroboyo account with efforts to maintain the Javanese dialect of Arek. The results of the study show that the AsliSuroboyo account consistently uses the Javanese dialect of Arek as a medium of communication. The use of Javanese dialect of Arek can not only be interpreted as an effort to maintain language as a communication tool, but can also be used as a means of showing regional identity. Through these efforts, followers of the AsliSuroboyo Instagram account can also feel attached and can introduce their regional identity to a wider scope.